Radiosurgery-induced early changes in peritumoral tissue sodium concentration of brain metastases - Ruder, Arne Mathias; Mohamed, Sherif A.; Hösl, Michaela; Neumaier-Probst, Eva; Giordano, Frank Anton; Schad, Lothar R.; Adlung, Anne (PLOS ONE, 2024)
Background Stereotactic radiosurgery (SRS) is an effective therapy for brain metastases. Response is assessed with serial 1H magnetic resonance imaging (MRI). Early markers for response are desirable to allow for individualized treatment adaption. Previous studies indicated that radiotherapy might have impact on tissue sodium concentration. Thus, 23Na MRI could provide early quantification of response to SRS. Purpose We investigated whether longitudinal detection of tissue sodium concentration alteration within brain metastases and their peritumoral tissue after SRS with 23Na MRI was feasible. Study type Prospective. Population Twelve patients with a total of 14 brain metastases from various primary tumors. Assessment 23Na MRI scans were acquired from patients 2 days before, 5 days after, and 40 days after SRS. Gross tumor volume (GTV) and healthy-appearing regions were manually segmented on the MPRAGE obtained 2 days before SRS, onto which all 23Na MR images were coregistered. Radiation isodose areas within the peritumoral tissue were calculated with the radiation planning system. Tissue sodium concentration before and after SRS within GTV, peritumoral tissue, and healthy-appearing regions as well as the routine follow-up with serial MRI were evaluated. Statistical tests Results were compared using Student’s t-test and correlation was evaluated with Pearson’s correlation coefficient. Results We found a positive correlation between the tissue sodium concentration within the peritumoral tissue and radiation dosage. Two patients showed local progression and a differing tissue sodium concentration evolution within GTV and the peritumoral tissue compared to mean tissue sodium concentration of the other patients. No significant tissue sodium concentration changes were observed within healthy-appearing regions. Conclusion Tissue sodium concentration assessment within brain metastases and peritumoral tissue after SRS with 23Na MRI is feasible and might be able to quantify tissue response to radiation.
Gesehen am 14.04.2025